"Everything is kind of the same except my mind is with me": exploring cannabis substitution in a sample of adults in early recovery from an opioid or stimulant addiction - Corinne A. Beaugard; Alexander Y. Walley; Maryann Amodeo (BMC, 2024)
Abstract Background Recovery from addiction is frequently equated with abstinence. However, some individuals who resolve an addiction continue to use substances, including via substitution (i.e., increased use of one substance after eliminating/ reducing another). Substitution may play a distinct role during early recovery (≤ 1 year), as this period is marked by dramatic change and adjustment. Cannabis is one of the most used substances and is legal for medical and recreational use in an increasing number of states. Consequently, cannabis an increasingly accessible substitute for substances, like fentanyl, heroin, cocaine and methamphetamine, with higher risk profiles (e.g., associated with risk for withdrawal, overdose, and incarceration). Methods Fourteen participants reported that they had resolved a primary opioid or stimulant addiction and subsequently increased their cannabis use within the previous 12 months. Using grounded theory, the interviewer explored their experiences of cannabis use during early recovery. Data were analyzed in three stages: line by line coding for all text related to cannabis use and recovery, focused coding, and axial coding to generate a theory about recovery with cannabis substitution. The motivational model of substance use provided sensitizing concepts. Results & discussion The final sample included eight men and six women ranging in age from 20 to 50 years old. Three participants resolved an addiction to methamphetamine and the remaining 11, an addiction to opioids. Participants explained that cannabis was appealing because of its less harmful profile (e.g., no overdose risk, safe supply, few side effects). Participants' primary motives for cannabis use included mitigation of psychiatric symptoms, withdrawal/ cravings, and boredom. While cannabis was effective toward these ends, participants also reported some negative side effects (e.g., decreased productivity, social anxiety). All participants described typical benefits of recovery (e.g., improved self-concept, better relationships) while continuing to use cannabis. Their experiences with and beliefs about substitution suggest it can be an effective strategy for some individuals during early recovery. Conclusions Cannabis use may benefit some adults who are reducing their opioid or stimulant use, especially during early recovery. The addiction field's focus on abstinence has limited our knowledge about non-abstinent recovery. Longitudinal studies are needed to understand the nature of substitution and its impact on recovery over time.